Risk assessment of exposure of healthcare providers in the context of SARS-CoV-2 - Salam Bani Hani; Salwa Al Obeisat; Lina Mrayan; Sanaa Abujilban; Jamila Abuidhail; Aysam I. Hweidi (Journal of Emergency Management, 2026)
Purpose: This study aims to determine the risk categorization of each healthcare worker (HCW) after exposure to a severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) patient and to inform the management of the exposed HCWs based on the risk they are exposed to.Design: A cross-sectional design was used, which was conducted in all healthcare facilities among SARS-CoV-2 patients.Methods: A self-administered tool in a Google Form® was used; the tool for risk assessment and management of exposure of HCWs in the context of SARSCoV-2, according to the World Health Organization guidelines, was used, which was completed by all HCWs who had been exposed to a patient with confirmed SARS-CoV-2 infection.Results: A total of 276 HCWs were recruited in this study. It was reported that the average age of participants was 36.1 years (standard deviation = 19.4). Most participants were female (n = 192, 69.6 percent) and resided inside Jordan (n = 245, 88.8 percent). It was reported that 222 (80.4 percent) of the HCWs were wearing single-use gloves during aerosol-generating procedures, and more than half of them were using N95 masks (n = 182, 65.9 percent) while caring for SARS-CoV-2 patients.Conclusion: An infection control system that allows for real-time monitoring and prompt correction by HCWs must take its place. This will keep HCWs informed of potential actions that could put them at risk of contracting the virus.Clinical evidence: Risk assessments facilitate early identification of potential exposures and ensure timely testing and isolation when needed, preventing further spread of SARS-CoV-2 within healthcare settings and the community.